Open and Distance Learning (ODL) during COVID-19: Challenges and Obstacles Among Nursing Students / Rusnani Ab Latif, Wan Ismahanisa Ismail - Ab Latif, Rusnani; Ismail, Wan Ismahanisa (UiTM Press, 2021)
Many countries, including Malaysia, have recently issued normative criteria that must be followed by all populations in the midst of the Covid-19 pandemic, which has turned into a global health crisis. As a result of the policy, several universities have chosen to use the open and distance learning (ODL) system to pursue non-face-to-face learning. E-learning is the most convenient way used by educators throughout the world to conduct academic sessions using various mediums as requires only internet access and telecommunication devices such as smartphones and laptops. However, there are many challenges and obstacles face by nursing students during ODL, such as poor internet connection and a lack of online educational resources; stress and anxiety during ODL learning; Social distancing; Financial constraints, and burnout from the workload of assignment. In conclusion, the Covid-19 pandemic had an impact on nursing students as a result of the barriers and challenges they faced when participating in online distance learning. Along with the challenges that nursing students are currently facing, lecturers must be prepared to equip themselves with knowledge and skills as well as new practices of teaching and learning that is relevant to the development and needs of the 21st century, thinking skills across all disciplines among nursing students should be given priority. The thinking skills of teachers and students, especially in the context of Higher Order Thinking Skills (HOTS) is a matter of necessity or priority in determining the successful transformation of education as outlined in the Blueprint 2013-2025.